"I'm mindfully green": examining the determinants of guest pro-environmental behaviors (PEB) in hotels. Issue 7 (2nd October 2020) - Dharmesti, Maria; Merrilees, Bill; Winata, Lanita
ABSTRACT: The paper examines the antecedents of Australian hotel consumer pro-environmental behaviors (PEB). The research investigates three forms of hotel guests' actual (self-reported) PEB: water-saving, energy-saving, and recycling behaviors. This study employs a hotel-customer survey in Australia (n = 339). A focus on green mindfulness is an innovative feature of the study. Interestingly, the results show green mindfulness to be the dominant predictor of hotel guests' PEB, followed by the individual's green habits at home. The findings address current environmental issues in the hotel industry and extend the literature of tourist sustainability on the actual PEB in a hotel context. Practically, this research contributes insights for hoteliers to understand guests' PEB so that they can improve their green programs.